An Evaluation of Concentration Risk Profile of Commercial Banks in India - Rekha (Indian Journal of Finance, 2009)
Concentration risk of a bank’s portfolio is the aggregation of transaction and intrinsic risk that results from loans to one borrower or one industry, geographic area, or line of business. Top management must define acceptable portfolio concentrations for each of these aggregations. The objective of this paper is to present a general framework for measurement of concentration risk followed by concentration risk profiling of public sector banks vis-Ã -vis private sector banks in India. A clear diagnosis of the character of concentration risk profile should help the bank management select a risk strategy that will be consistent with long-term objectives for portfolio quality and performance. The selection of the appropriate strategy i.e., conservative, managed or aggressive, depends on a bank’s priorities and risk appetite. The results of the study would enable tracking the trend in concentration risk of credit portfolio of commercial banking industry in India. Besides, the results indicate clearly the character of concentration risk profile of public sector banks vis-Ã -vis private sector banks in India.